The use of local raw materials and fermented feeds for the growth of Giant Prawns (Macrobrachium rosenbergii). Issue 1 (1st July 2022) - Mulyasari,; Setijaningsih, L; Samsudin, R; Taufik, I; Kusmini, I I
Abstract: The purpose of this study was to evaluate the effect of local raw materials feed and fermented feed on the growth of giant prawns. This study was conducted using a completely randomized design (CRD) consisting of 3 treatments with 3 replications, each treatment was (A) commercial feed as a control; (B) feed based on local raw materials and (C) feed based on fermented local raw materials. The study was conducted at Sukawening Village, Dramaga District, Bogor Regency. The giant prawn that used has an initial weight of 0.31±0.005 g with stocking density of 50 fish/m2. The container used was a tarpaulin pond measuring 2x3x0.5m2. The study was conducted for 53 days. Observation variables include growth parameters, feed conversion, protein and fat retention, body amino acids and digestive tract enzyme activity. The results showed that feed based on local raw materials was able to produce relative growth (620±10.43%), specific growth rate (3.80±0.28%/day), protein retention (43.26%) and fat retention (36.1%) higher than other treatments and gave the lowest feed conversion value (1.07) compared to commercial feed and feed based on fermented local raw materials. These results indicate that feed based on local raw materials potential to be applied to giant prawn culture.